Pengaruh Faktor Audit dan Karakteristik Perusahaan Terhadap Financial Restatement - Nadya Annida; Ratna Anggraini; Hafifah Nasution (LPPM Universitas Negeri Jakarta, 2026)
This study analyzes the predictive power of audit report lag, key audit matters (KAM) disclosure, firm size, and leverage toward financial restatement. Data compilation follows a quantitative path, utilizing secondary sources from audited annual disclosures of IDX-listed corporations in the infrastructure, basic materials, consumer cyclicals, and consumer non cyclicals sectors from 2023 to 2024. The final sample incorporates 364 enterprises, accumulating 728 firm-year observations selected via purposive sampling. Statistical estimations executed through logistic regression (IBM SPSS Statistics 29) show that audit report lag, KAM disclosure, and organizational size all have positive and significant impacts on the occurrence of financial restatement. Meanwhile, leverage does not play a significant role. These findings reinforce agency arguments that audit-related complexities and scale-driven transactions heavily influence financial reporting adjustments in emerging economies.